2020
DOI: 10.1007/s00192-020-04396-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term mesh complications and reoperation after laparoscopic mesh sacrohysteropexy: a cross-sectional study

Abstract: Introduction and hypothesis The paucity of long-term safety and efficacy data to support laparoscopic mesh sacrohysteropexy is noteworthy given concerns about the use of polypropylene mesh in pelvic floor surgery. This study is aimed at determining the incidence of mesh-associated complications and reoperation following this procedure. Methods This was a cross-sectional postal questionnaire study of women who underwent laparoscopic mesh sacrohysteropexy between 2010 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…There were no mesh exposures in the MeshH group, similar to the largest reported cross-sectional study for mesh hysteropexy [20]. Pelvic pain was reported by 3% in the MeshH group with no requests for mesh removal.…”
Section: Discussionsupporting
confidence: 70%
“…There were no mesh exposures in the MeshH group, similar to the largest reported cross-sectional study for mesh hysteropexy [20]. Pelvic pain was reported by 3% in the MeshH group with no requests for mesh removal.…”
Section: Discussionsupporting
confidence: 70%
“…Nightingale and Phillips examined 93 of 112 patients over 9 years of age (mean 6 years follow-up) and reported only one mesh complication (bowel obstruction). We did not find any mesh complication yet and hope to publish a long term follow up soon [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The long-term repeat surgery rate was found to be quite low (3.2%) with the laparoscopic smSHP technique. Previous studies of dual-mesh SHP procedures reported repeat surgery rates between 0% to 13.6% in both short-and longterm follow-up studies (Rahmanou et al, 2014;Jefferis et al, 2017;Lone et al, 2018;Izett-Kay et al, 2020). Jefferis et al (2017) reported repeat apical prolapse surgery in 2.8% and repeat anterior repair in 7.1%, at 10-years follow-up.…”
Section: Discussionmentioning
confidence: 93%